Experimental investigation of the energy performance of a novel Micro-encapsulated Phase Change Material (MPCM) slurry based PV/T system. (1st March 2016) - Qiu, Zhongzhu; Ma, Xiaoli; Zhao, Xudong; Li, Peng; Ali, Samira
Highlights: An experimental investigation to a novel MPCM slurry based PV/T system was conducted. The system had the reduced solar efficiency at a higher solar radiation. The system had the increased solar efficiency at a higher slurry Reynolds number. The most favourite MPCM concentration was around 10%. The experimental results approved the accuracy of the established computer model. Abstract: As a follow-on work of the authors' theoretical study, the paper presented an experimental investigation into the energy performance of a novel PV/T thermal and power system employing the Micro-encapsulated Phase Change Material (MPCM) slurry as the working fluid. A prototype PV/T module of 800 mm × 1600 mm × 50 mm was designed and constructed based on the previous modelling recommendation. The performance of the PV/T module and associated thermal and power system were tested under various solar radiations, slurry Reynolds numbers and MPCM concentrations. It was found that (1) increasing solar radiation led to the increased PV/T module temperature, decreased solar thermal and electrical efficiencies and reduced slurry pressure drop; (2) increasing the slurry Reynolds number led to the increased solar thermal and electrical efficiencies, decreased module temperature, and increased pressure drop; and (3) increasing the MPCM concentration led to the reduced module temperature and increased pressure drop. The experimental results were used to examine the accuracy of the established computer model, giving a derivation scale ranging from 1.1% to 6.1% which is an acceptable error level for general engineering simulation. The recommended operational conditions of the PV/T system were (1) MPCM slurry weight concentration of 10%, (2) slurry Reynolds number of 3000, and (3) solar radiation of 500–700 W/m 2 ; at which the system could achieve the net overall solar efficiencies of 80.8–83.9%. To summarise, the MPCM slurry based PV/T thermal and power system is superior to conventional air-sourced heat pump systems (ASHP) and solar assisted heat pump systems (ISAHP), and has the potential to help reduce fossil fuel consumption and carbon emission to the environment.